A method for scale‐up of co‐electrospun nanofibers via flat core‐shell structure spinneret. Issue 21 (13th June 2014) - Wu, Huihui; Zheng, Yuansheng; Zeng, Yongchun
ABSTRACT An approach to the scale‐up of co‐electrospinning via a flat core‐shell structure spinneret has been developed in this study. The spinneret with a flat surface involves shell‐holes and core‐needles. Electric field simulation reveals that the flat core‐shell spinneret configuration creates a more uniform electric field gradient. Experimental study shows that in comparison with the conventional needle co‐electrospinning, core‐shell nanofibers produced by this new designed setup are finer and of better morphology. Composite nanofibers with special morphologies can be fabricated by modifying the structure of this spinneret. The production rate of the core‐shell nanofibers can be enhanced by increasing the hole and needle number of the spinneret. This novel design is expected to provide a promising method towards the massive production of core‐shell nanofibers. © 2014 Wiley Periodicals, Inc. J. Appl. Polym. Sci. 2014, 131, 41027.